Examining What Makes Violent Crime Victims Unique: Extending Statistical Methods for Studying Specialization to the Analysis of Crime Victims - Schreck, Christopher J. (Journal of quantitative criminology, 2012)
Objectives Much victimization research focuses on specific types of crime victims, which implies that the factors responsible for some victimization outcomes are distinct from others. Recent developments in victimization theory, however, take a more general approach, postulating that victimization regardless of type will share a similar basic etiology. This research examines how and whether the risk factors that are associated with violent victimization significantly differ from those that predict nonviolent victimization. Methods Using data from 3,682 Kentucky youth, we employ Osgood and Schreck’s ( 2007 ) Item Response Theory-based statistical approach for detecting specialization to determine the properties and predictors of tendencies for individuals to fall victim to specific types of crime. Results Findings show that victims typically experience varied outcomes, but some victims have a clear tendency toward violent victimization and that it is possible to predict this tendency. Conclusions The findings indicate that a more nuanced general approach, one that accounts for tendencies toward specific victimization outcomes, might add insight about the causes of victimization. This research also shows how statistical methods designed to examine offense specialization can add value for research on victimization.